A Project Feasibility Study on Stain Away Multi-Purpose Instant Stain Remover - Rodriguez, Sharmaine Dabela (College of Engineering, 2003)
Household cleaning is one of the critical activities inside the Filipino homes. Detergents, bleaching products and other multi-purpose cleaners are widely used in removing stains and dirt from carious surfaces. This practice requires a lot of time and effort, thus yielding to a considerable cost. In the international market, variations of household cleaners are currently available. One of which is the instant stain remover. This type of cleanser instantly removes stains and dirt from surfaces without the use of water, protecting the surface from further damage by preventing the stain from penetrating the surface. This study aims to determine the feasibility of introducing instant stain removers as a breakthrough product and maintain a considerable position in the local market. The study encompasses various stages, namely, market, technical, financial and the social profitability studies. Stain Away Multi-Purpose Instant Stain Remover is a liquid stain remover that could cleanse almost all types of surfaces and remove all kinds of dirt. It does not require the use of water and further washing. Its main component is d? limonene, which is oil extracted from citrus. It is a known ingredient for effective cleaning and other purposes such as orange fragrance to products, cooling fluids and as a straight solvent. Stain Away is packed in various sizes using recycled PET bottles. In the market study, the market opportunities and marker share were determined. Marketing strategies were also formulated in order to be able to bring the product to its target market. Marketing plan and budget were also developed. Telephone survey was conducted in order to determine the demand for the product. The target market was determined to be households, working individuals and students. Projected demand of 5,013,994 bottles for 2003 up to 6,494,506 bottles for 2007 was determined for the 5 year period of the study. The market share for the households, students and working individuals were 5.6%, 47.3% and 32.2% respectively. Having determined these important factors, it was concluded that the product was feasible in the market aspect. Thus, the technical study would be pursued. Technical study was performed in order to determine the specific details of the building the company, from the main ingredient up to delivery of the product. The raw materials, production process, the machines and equipment were identified for the manufacturing of Stain Away. Included also in the technical study are the determination of capacity requirements and inventory level. The production labor needs and the organization most suited for the company, which is vertical organization were developed. The facility location and layout were also drawn for the company. Lastly, the project cost for the company was determined to be Php 27,343,662.82, considering everything necessary in its establishment. Having done the technical study, wherein the project was concluded to be technically feasible, the financial analysis was next performed. In this stage, sources of the financing needs were identified. The project?s profitability was determined using various financial forms, such as the pro-forma income statement, balance sheet and cash flows. Net profit of Php 47,660,558.97 for 2003 up to Php 62,233,854.77 for 2007 was projected for the company with an increasing trend for the study period of 5 years. From the financial analysis, the company passed all the tests performed, from the test of liquidity up to test of capital investment. Sensitivity analysis was performed in order to determine the flexibility of the then company while maintaining its profitability. Net present value of Php 24,637,536.20, an Internal rate of return of 95.376%. The results of the analyses in the financial study all support to conclude that the company is indeed financially profitable. As the final stage of the study, the social attractiveness of the company was established in the Social Analysis. The benefits and costs to the social community that the project could contribute were determined. For the study period, the benefits were improved standard of living through the new employment, patronization of local products, and increase in government funds through the taxes. As for the costs for the company, the total project cost was considered. To further prove the social attractiveness of the company, the socio-economic criteria were used. A Net Present Value of Php 18,174,344.98, Internal Rate of Return of 62.49% and a benefit-cost ratio of 5.420 were computed. All of these values prove that the project is indeed socially profitable. To sum it all up, establishing Stain Away Multi-Purpose Instant Stain Remover in the local market as a breakthrough product, having done all the necessary study and analyses, is indeed very feasible.